Answer:
see explanation
Explanation:
Using the identities
1 + cot²x = cosec²x
cosec²x =
, cotx =
![(cosx)/(sinx)](https://img.qammunity.org/2022/formulas/mathematics/high-school/o7bemuxec08z700vffsduqzyb3xvcyc2c7.png)
Consider the left side
cos²A + cos²A cot²A ← factor out cos²A from each term
= cos²A(1 + cot²A)
= cos²A × cosec²A
= cos²A ×
![(1)/(sin^2A)](https://img.qammunity.org/2022/formulas/mathematics/high-school/3aozbo70ymfixbn72hq91mq8zazkoxtztc.png)
=
![(cos^2A)/(sin^2A)](https://img.qammunity.org/2022/formulas/mathematics/high-school/sakbji90m25d9hruy3384u8n95cl9xrbgi.png)
= cot²A
= right side , thus proven